Comment about the use of unconventional Tauc plots for bandgap energy determination of semiconductors using UV–Vis spectroscopy - Peverga R. Jubu; E. Danladi; U.I. Ndeze; O. Adedokun; S. Landi, Jr.; A.J. Haider; A.T. Adepoju; Y. Yusof; O.S. Obaseki; F.K. Yam (Results in Optics, 2024)
The Tauc method is the conventional technique for estimating the accurate optical bandgap energy of semiconductors using UV–Vis spectroscopy. The proper bandgap is usually determined by directly extrapolating the linear region of the optical spectrum to the horizontal axis of the Tauc plot αhv1/r vs. hv. However, the use of unconventional Tauc plots, such as α1/r vs. hv, A1/r vs. hv, and FR∞ vs. hv are also found in the literature. This raises a debate as to whether these nontraditional methods can produce the correct bandgap value. These uncommon methods appear frequently even in recent papers published in reputable journals, and therefore, have raised concern to investigate the likelihood of obtaining the correct bandgap value using the unusual methods. Results showed that the plots of α1/r vs. hv, and A1/r vs. hv yielded bandgap values that were consistent with those deduced from the universal Tauc plot, whereas the other methods failed.